What affects the ability to accumulate the best applicants by Russian universities? The application of quantile regression model - Edyta Łaszkiewicz; Stepan Zemtsov; Vera Barinova (Comparative Economic Research. Central and Eastern Europe, 2016)
The aim of this paper is to evaluate which university's characteristics have the greatest impact on the competitiveness of universities in their ability to attract better students in Russia. We examined the impact of three groups of factors,related to teaching, research and entrepreneurial activities of universities. The quantile regression model was applied for the subsample of public and private higher education institutions localized in Russia. The results prove that not only traditional, teaching-related factors affect the attractiveness of the universities. We found that the research quality and entrepreneurial experience both increase the ability to accumulate the best applicants by Russian universities. However, the synergy between training, research and business activities is not always achieved. The importance of science and business-oriented activities varies between public and private institutions. According to the results from the quantile regression the importance of the certain factors differs between the quantiles of the dependent variable distribution. Our findings might be useful for the governmental authorities during the universities' assessment as well as for the higher education institutions themselves - in order to define their strategic development and attract better students.
Keywords: 330; higher education institution; universities' competitiveness; Russian education system; students; quantile regression